Geospatial Data Management at Iphan: Trajectory, Challenges and Perspectives (FIG Joint Land Administration Conference, 2025)
The National Institute of Historic and Artistic Heritage (Iphan), established in 1937, plays a central role in preserving Brazil’s cultural heritage. Throughout its history, the institution has progressively incorporated the use of geospatial data, transitioning from analog records to digital systems in line with advances in information technologies. This article discusses Iphan’s trajectory in the territorial management of cultural assets, addressing historical, normative, and technological achievements that have shaped its practices of documentation, protection, and oversight. It presents the main systems and tools developed for handling geospatial data, as well as the institutional and technological challenges that influence their consolidation. The study aims to contribute to the debate on the modernization of cultural heritage management by situating Iphan within the broader context of national geoinformation policies and its integration into the National Spatial Data Infrastructure (INDE).